1998
DOI: 10.1084/jem.188.6.1159
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope Glycoprotein Ectodomains Determine the Efficiency of CD4+ T Lymphocyte Depletion in Simian– Human Immunodeficiency Virus–Infected Macaques

Abstract: SummaryCD4 ϩ T lymphocyte depletion in human immunodeficiency virus type 1 (HIV-1)-infected humans underlies the development of acquired immune deficiency syndrome. Using a model in which rhesus macaques were infected with chimeric simian-human immunodeficiency viruses (SHIVs), we show that both the level of viremia and the structure of the HIV-1 envelope glycoprotein ectodomains individually contributed to the efficiency with which CD4 ϩ T lymphocytes were depleted. The envelope glycoproteins of recombinant S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 46 publications
9
127
1
Order By: Relevance
“…The acquisition of these unusual pathogenic characteristics appears to be multigenic: 42 amino acid substitutions, relative to the starting nonpathogenic SHIV DH12 clone (20), distributed among several viral genes, were present in SHIV DH12R-CL-7 . In contrast to studies of the envelope glycoproteins associated with molecularly cloned SHIV KB9 and SHIV HXBc2P-3.2 , which were reported to be the principal determinants inducing CD4 ϩ T-lymphocyte depletion (4,15), the entire env gene of SHIV DH12R-CL-7 , by itself, failed to confer the rapid and irreversible CD4 ϩ T-cell-depleting properties following its insertion into the genome of nonpathogenic parental strain SHIV DH12 . Similarly, substitution of gag-pol sequences from pathogenic SIV E543 could not replace analogous SIV mac239 genes in SHIV DH12R-CL-7 .…”
Section: Vol 78 2004mentioning
confidence: 77%
See 2 more Smart Citations
“…The acquisition of these unusual pathogenic characteristics appears to be multigenic: 42 amino acid substitutions, relative to the starting nonpathogenic SHIV DH12 clone (20), distributed among several viral genes, were present in SHIV DH12R-CL-7 . In contrast to studies of the envelope glycoproteins associated with molecularly cloned SHIV KB9 and SHIV HXBc2P-3.2 , which were reported to be the principal determinants inducing CD4 ϩ T-lymphocyte depletion (4,15), the entire env gene of SHIV DH12R-CL-7 , by itself, failed to confer the rapid and irreversible CD4 ϩ T-cell-depleting properties following its insertion into the genome of nonpathogenic parental strain SHIV DH12 . Similarly, substitution of gag-pol sequences from pathogenic SIV E543 could not replace analogous SIV mac239 genes in SHIV DH12R-CL-7 .…”
Section: Vol 78 2004mentioning
confidence: 77%
“…Although these changes were distributed throughout the viral genome, they primarily affected the env and nef genes. On the basis of increased chemokine receptor binding affinity, membrane fusion capacity, and/or neutralization resistance, earlier analyses of the molecularly cloned SHIV KB9 derivative of SHIV 89.6P (15) and the molecularly cloned SHIV HXBc2P-3.2 derivative of SHIV KU-1 (4) concluded that FIG. 3.…”
Section: Pathogenicity Of Cloned Shivs In Rhesus Monkeysmentioning
confidence: 99%
See 1 more Smart Citation
“…Subject Mm18284 was infected with SHIV-KB9ct, and subject Mm19941 was infected with SHIV-KB9(Ϫ305). Some immunologic and virologic data from these monkeys have been previously reported (42,45,47). Infection of both animals was confirmed by serologic and virologic assays (45,47).…”
Section: Shiv Clones Animal Infections and Sample Handlingmentioning
confidence: 81%
“…SHIV-KB9ct and SHIV-KB9(Ϫ305) are hybrid viruses that combine aspects of the parental Ϫ89.6 and more pathogenic ϪKB9 clones. These viruses were selected for the present study because they expressed a gp120 identical with or cross-reactive with that of the rgp120-89.6 used as an inverse immunohistochemical probe and show increased pathogenicity compared with the parental SHIV-89.6 (45,47).…”
Section: Shiv Clones Animal Infections and Sample Handlingmentioning
confidence: 99%